2008
DOI: 10.17305/bjbms.2008.2996
|View full text |Cite
|
Sign up to set email alerts
|

Should Diagnostic Hysteroscopy be a Routine Procedure During Diagnostic Laparoscopy in Infertile Women?

Abstract: The aim of this study was to clarify the role of simultaneous combined diagnostic approach using laparoscopy and hysteroscopy in the evaluation of female infertility. In a retrospective study, 360 infertile women underwent complete fertility evaluation. All the patients were examined by simultaneous combined laparoscopy and hysteroscopy as a part of the routine infertility evaluation. Laparoscopy and hysteroscopy were successful in 360 patients. Bilateral tubes were blocked in 18 (5%) and unilateral tubal occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 12 publications
7
40
1
2
Order By: Relevance
“…Our results at laparoscopy and dye studies had shown bilateral tubal patency in 87 (92.5 %), bilateral tubal block in 4 (4.3 %) and unilateral tubal block in 3 (3.2 %) of infertile patients, excluding those who had come for recanalization. In one study at laparoscopy, bilateral tubal patency was demonstrated in 86.67 %, bilateral tubal block in 5 % and unilateral block in 8.33 % of patients [9]. In our study, pelvic pathology by laparoscopy was confirmed in 51.7 % of our cases, which was similar to other studies [16,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results at laparoscopy and dye studies had shown bilateral tubal patency in 87 (92.5 %), bilateral tubal block in 4 (4.3 %) and unilateral tubal block in 3 (3.2 %) of infertile patients, excluding those who had come for recanalization. In one study at laparoscopy, bilateral tubal patency was demonstrated in 86.67 %, bilateral tubal block in 5 % and unilateral block in 8.33 % of patients [9]. In our study, pelvic pathology by laparoscopy was confirmed in 51.7 % of our cases, which was similar to other studies [16,17].…”
Section: Discussionsupporting
confidence: 91%
“…Septate uterus is the most common uterine anomaly with a mean incidence of approximately 37.15 % followed by bicornuate uterus approximately 26.13 % and arcuate uterus approximately 21.26 % of uterine anomaly in infertile couple [9]. Our study shows that the incidence of uterine anomaly was 13 (13.8 %).…”
Section: Discussionmentioning
confidence: 49%
“…9 In our study, pelvic pathology by laparo-scopy was confirmed in 59.5% of our cases, which was similar to other studies. 16,17 Thus, diagnostic laparoscopy is the standard means of diagnosing the tubal pathology, peritoneal factors, ovarian factors and uterine factors as cause of infertility.…”
supporting
confidence: 92%
“…9 Present study shows that the incidence of uterine anomaly was 54 (11.1%). Septate uterus is the most common anomaly with a mean incidence of approximately 37 (67.8%).…”
Section: -8mentioning
confidence: 61%
“…1 It is present in 1-10% of unselected population, 2-8% of infertile women and 5-10 % of women with the history of miscarriage. [2][3][4][5][6][7][8][9][10][11][12] The wide range of difference in the prevalence rate is presumably because of use of different classification systems and non-uniform diagnostic tests. 13 Normal development of the female reproductive tract involves a series of complex processes which includes differentiation, migration, fusion and canalization of the Mullerian system.…”
Section: Introductionmentioning
confidence: 99%